Adrenocortical Carcinoma Basic Science and Clinical Concepts - Hammer, Gary D.; Else, Tobias; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
This first edition of the textbook (3z(BAdrenocortical Carcinoma: Basic Sciences and Clinical Concepts(3y (Bprovides a concise compilation of relevant data advancing our current understanding of this rare cancer. Chapters are dedicated to various aspects of both the basic biology and the clinical science relating to adrenocortical carcinoma (ACC). Expert clinicians introduce the reader to current state-of-the-art clinical care of patients with ACC. As a considerable body of knowledge on ACC has accumulated over the last decades, expert scientists have authored additional sections that serve as a reference source for the experienced researcher as well as an introduction for the trainee in the laboratory or clinic. Clinical topics span the epidemiology, diagnosis and therapy of ACC. Scientific topics areas span the pathology and pathophysiology of ACC with a special focus on experimental models of adrenocortical tumors and recent advances in the genetic aspects and signaling pathways in ACC. The content of this book was compiled and edited with the intent of facilitating the translation of knowledge into future diagnostic and therapeutic tools that will ultimately improve patient care.s
Keywords: Medicine; Cancer research; Pharmacology; Biomedicine; Cancer Research; Pharmacology/Toxicology.; Electronic books